Shadows and policy gaps around Spanish criminal criminal responsibility of minors (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
Spanish penal Code, in force since 1995, disposes that those minors than 18 years penal liability be regulated by a special statute, which has been promulgated asL.O. 5/2000, of January 12th. This act’s purpose, according to Spanish legal tradition,is educative and corrective, not punitive and proportional to guilt like Code punishments. Nevertheless, society has reacted against above mentioned act, thinkingthat it is too soft to brake juvenile delinquency increase and legislator has followed this line, promulgating several reforms of that act between 2000 and 2006 (the first and second reforms before the beginning of the act’s force), which have hardened minors penal liability. The present work tries to show that those reformsare unconstitutional, unlawful, immoral and inopportune, because of opposition to international treaties regulating rights and duties of children, penal regulations cannot be applied to minors than 18 years, absence of punishments against persons who are incessantly inciting children to violence, and configuration of criminal law against minor delinquents as an example of “criminal law for enemies” and not“criminal law for citizens”, following the most recent doctrinal guidelines.
Keywords: minor; imputability; penal responsibility; top interest of the minor; Purposes of a sentence